Effect of induction moment on Bradyrhizobium-soybean (Glycine max) interaction - Nápoles-García, Maria Caridad; Costales-Menéndez, Daimy; Hernández-Forte, Ionel; Pérez-Pérez, Reneé; Wegria, Guilleaume; Cabrera-Pino, Juan Carlos (Agronomía Mesoamericana, 2022)
Introduction. Legume nodulation is regulated by the exchange of molecular signals between the plant and rhizobia. The bacterial nodulation genes are activated by flavonoids present in root exudates. As a result of this activation, the Nod factors are synthesized, which in turn participate in the morphogenesis and function of the nodules. It is then possible to regulate the induction of Nod factors and other signals related to the nodulation process, during the inoculants production. Objective. To determine if the moment to induce the nodulation genes in Bradyrhizobium inoculants affects the synthesis of compounds related to the nodulation process and its interaction with soybean plants. Materials and methods. The research was developed in Rizobacter S.A., Argentina and Fyteko S.A. laboratories, Belgium, and in a plant growth chamber of the first one, during May-June of 2017. Two Bradyrhizobium strains were induced with daidzein in three moments. The signals produced by the strains and the biological effect in soybean plants were studied. Results. Differences were detected in the molecules produced by the bacteria, but it did not affect the growing and plants nodulation related to the different moments of induction. Conclusion. The metabolites excreted by Bradyrhizobium changed with strain and induction moment, although the latter did not affect nodulation or soybean plants growth.